The Enduring Legacy of the First Nesvizh Radziwill Ordination Library in Lithuania: Results of Recent Research - Misiūnienė, Jadvyga (Knygotyra, 2024)
The year 1749 is considered the beginning of the Nesvizh Radziwill Ordination Library. It was in this year that, by order of Michał Kazimierz Radziwiłł ‘Rybeńko’ (1702–1762), the Grand Hetman of Lithuania and Voivode of Vilnius, a new building was erected in Nesvizh specifically for the castle’s library. The Grand Ducal Library established there accumulated three collections of books: the old Nesvizh collection, the Biały Palace collection, and the collection of Jacob Heinrich von Flemming (1667–1728), the former Prime Minister of Augustus II and brother-in-law of Radziwiłł ‘Rybeńko’. In 1772, the Radziwiłł Ordination Library – the largest private book collection in the entire Polish-Lithuanian Commonwealth at the time – was taken away from Nesvizh by the Russian army as a war trophy. This article discusses the legacy of the First Nesvizh Radziwiłł Ordination Library that has survived in the libraries of Lithuanian memory institutions and private collections. It examines the provenance marks of the books, compiles a bibliographic list of books (manuscripts), and supplements it with new findings. Based on the results of historical and provenance research, some erroneous statements that have persisted in Lithuanian historiography have been corrected.
Keywords: Lithuanian cultural heritage; Grand Duchy of Lithuania; manor libraries; Nesvizh Castle library; Radziwiłł family; Michał Kazimierz Radziwiłł ‘Rybeńko’; old books; provenance; ex-libris